2007
DOI: 10.1243/09544070jauto482
|View full text |Cite
|
Sign up to set email alerts
|

Collapse study of thin-walled polygonal section columns subjected to oblique loads

Abstract: The present paper deals with the collapse simulation of aluminium alloy extruded polygonal section columns subjected to oblique loads. Oblique load conditions in numerical simulations are applied by means of impacting a declined rigid wall on the tubes with no friction in this task. The explicit finite element code LS-DYNA is used to simulate the crash behaviour of polygonal section columns that are undergoing both axial and bending collapse situations. In order to validate LS-DYNA results the collapse procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…(4) It is seen that different cross-sectional geometries with the same cross-sectional area have no remarkable effect on energy absorption and force response. This result is contrary to the literature report about cross-sectional effect for small tubes which are used for energy absorption in vehicles' structures [3]. This difference may be a result of the big size of the box used as the internal layer of studied nose.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…(4) It is seen that different cross-sectional geometries with the same cross-sectional area have no remarkable effect on energy absorption and force response. This result is contrary to the literature report about cross-sectional effect for small tubes which are used for energy absorption in vehicles' structures [3]. This difference may be a result of the big size of the box used as the internal layer of studied nose.…”
Section: Discussioncontrasting
confidence: 93%
“…In the first phase of the investigation, the LS-DYNA simulation results were validated with experimental dynamic impact test data published by Seitzberger et al [3]. These authors have carried out experimental investigations in order to study the effects of different tube-and-filler arrangements on the crushing behaviour of axially compressed tubular crush elements.…”
Section: Numerical Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the mentioned manufacturing benefits, new interesting thinwalled structures made of aluminum have been introduced by the researchers to further improve the crashworthiness capacity and automobile safety. For example, Hosseini-Tehrani and Pirmohammad (2007Pirmohammad ( , 2010Pirmohammad ( , 2011 studied crushing behavior of aluminum extruded tubes with different cross-sectional shapes. In another study, Esmaeili-Marzdashti et al (2017) investigated crashworthiness of the S-shaped octagonal tubes with different cross-sections.…”
Section: Introductionmentioning
confidence: 99%
“…There existed a critical or threshold angle, which was a transition between progressive collapse and lateral bending modes. Hosseini-Tehrani and Pirmohammad [21]investgated the effect of loading angle on mean crush loads and permanent displacements for square, hexagonal, octagonal and decagonal tubes, and showed that the octagonal cross-section has better characteristics from the point of view of vehicle crashworthiness under oblique load conditions. Qi et al [22] provided a comparative study on the crashworthiness of four types of square tubes, namely single-cell straight, single-cell tapered, muti-cell straight and muti-cell taper, under oblique loading.…”
Section: Introductionmentioning
confidence: 99%